A Study of E-Banking Services in Public Sector Banks in India - Saraswati, Saraswati; Singh, Netra Pal (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
Bankers in India provide ease of service by utilizing information technology for safe and appropriate transaction services. With this paradigm change in view, this research paper embodies the analysis of three dimensions/factors of e-banking: accessibility, convenience, and security, and the impact of these factors on customer satisfaction. The study is based on the secondary and primary data collected with a structured questionnaire from 165 respondents in the vicinity of the district of Palwal, Haryana. The public sector banks and respondents were selected using the criteria of the convenience sampling method. The data was collected on 17 statements of inherent three dimensions on a 5-point Likert scale and three statements of customer satisfaction dimension. The collected data was subjected to inferential statistics and dimension reduction/factor analysis. The results indicate a positive contribution of three latent variables towards the overall satisfaction of customers of public sector banks in India.